Construction of Mas'uliyah Spiritual Values in Transformational Leadership - Bambang Widarno; Olivia Fachrunnisa; Ardian Adiatma (Al Tijarah, 2024)
Transformational leadership (TL) is known as a change facilitator because it contributes a lot to organizational culture and is effective for organizational improvement. The stability of the TL concept still contains weaknesses and is widely criticized for self-efficacy bias, evangelical, lacks conceptual clarity, is anti-democratic, solitary, and does not have checks and balances. A model that is more perfect and complete in dimensions is needed by adding transcendental values, which are not only oriented towards methods or processes and achieving goals, but must also be based on religious (spiritual) values that combine 3 elements: morality, awareness, and faith. By believing that Allah will hold humans accountable in the hereafter, we propose the Mas'uliyah Transformational Leadership (MTL) leadership concept. The synthesis of the TL dimension with the Islamic values of mas'uliyah produces four new dimensions: mas'uliyah idealized influence, mas'uliyah inspirational motivation, mas'uliyah intellectual stimulation, and mas'uliyah individual consideration. The new concept of religious-based leadership needs to be proven empirically in an institution or community.